Zic1 suppresses gastric cancer metastasis by regulating Wnt/β‐catenin signaling and epithelial‐mesenchymal transition. Issue 2 (2nd January 2020) - Ge, Qiwei; Hu, Yingying; He, Jiamin; Chen, Fei; Wu, Lunpo; Tu, Xintao; Qi, Yadong; Zhang, Zizhen; Xue, Meng; Chen, Shujie; Zhong, Jing; Wang, Liangjing
Abstract: Gastric cancer (GC) patients with metastasis had limited treatment options and dismal outcome. We have previously reported the aberrant expression of Zic family member 1 (Zic1) in GC. However, the functional roles and underlying mechanism of Zic1 in GC metastasis remain unknown. Here, we demonstrate that lower expression of Zic1 was correlated with more lymph node metastasis and poor outcome of GC patients. Ectopic expression of Zic1 suppressed both lung metastasis and peritoneal tumor dissemination of GC in mice. The metastatic suppressing ability of Zic1 was mediated by regulating the process of cell invasion, adhesion and epithelial‐mesenchymal transition (EMT). Mechanistically, Zic1 could downregulate Wnt targets including c‐Myc and Cyclin D1 by inhibiting LEF transcriptional activity in GC cells. Notably, Zic1 was inversely related to the expression of Cyclin D1 in GC tissues tested. In addition, Zic1 could physically interact with β‐catenin/transcription factor 4 (TCF4) and disrupt their complex formation, while not affecting β‐catenin nuclear localization. Collectively, our study indicated that Zic1 suppressed GC metastasis through attenuating Wnt/β‐catenin signaling and the EMT process. Our work may provide novel therapeutic strategies for the metastasis of GC.